The Effect of Social Media Marketing Towrds Customer-Brand Engagement : The Phenomenon in Luxury Fashion Bags Brand’s in Jakarta - Karimah Karimah; Diana Sari (STIKes Ibnu Sina Ajibarang, 2024)
This study examines the effect of social media marketing on customer-brand engagement in the luxury fashion bags sector in Jakarta. By leveraging the growing importance of social media as a marketing tool, this research aims to understand how various dimensions of social media marketing—entertainment, customization, interaction, electronic word-of-mouth (eWOM), and trendiness—influence customer-brand engagement and self-brand connection. Using a quantitative approach, data was collected through surveys distributed to consumers of luxury fashion bags in Jakarta. The analysis reveals a positive correlation between social media marketing efforts and customer-brand engagement, with self-brand connection acting as a significant mediating factor. The findings highlight the necessity for luxury brands to strategically utilize social media to enhance consumer relationships and engagement, providing practical insights for marketers in optimizing their social media strategies.